Optimization of pore size and filter material for better enrichment of environmental DNA - Liu, Qianqian; Tan, Juan; Wang, Min; Xin, Ni; Qi, Rui; Wang, Hui (Frontiers in Environmental Science, 2024)
In the study of environmental DNA (eDNA), the rate of water filtration and the amount of DNA obtained are of general interest to researchers. We compared the PCTE filters with different pore sizes in enriching total DNA and fish eDNA from water samples. We also designed and tested a new filter device with a PET pad (5 µm) superimposed on a PCTE membrane (3 µm) and compared it to a pure PCTE filter. A comprehensive evaluation of filtration time, eDNA concentration, fish DNA quantification, and fish species detected showed that the shortest average filtration time was obtained with the 8 μm pore size (2 min 9 s) and the longest average filtration time was obtained with the 0.2 μm pore size (32 min 6 s). The highest average DNA concentration was 3.785 ng/µl for the 0.2 μm filter and the lowest was 0.577 ng/µl for the 8 μm filter; meanwhile, the concentrations of fish DNA measured by quantitative PCR were 5.02E+02(8μm), 4.79E+02(3μm), 1.63E+03(1.2μm), 5.95E+03(0.2μm) copies of fish DNA per µl and there was no significant difference in the results between them (p>0.05). The sequencing results showed that 17 fish species were detected in the 0.2μm filter, 10 species in the 1.2μm filter, 12 species in the 3μm filter and 11 species in the 8μm filter. Comparing to 3 µm and 0.2 um, the average filtration time in stacked-filter was reduced by 4 and 24 minutes, respectively, while the average concentration was 2.46 and 1.55 times higher than the former. The qPCR results showed that the number of eDNA copies of the samples enriched with the 3 µm and stacked-filter was 4.79E+02 and 1.53E+04, respectively. 3 µm and stacked-filter showed significant differences (P < 0.05), while 0.2 µm and stacked-filter did not show significant differences (P > 0.05). Sixteen fish species were detected by the stacked-filter. The number of eDNA obtained and the number of fish species detected were higher than those of the pure PCTE filter, while clogging during filtration was effectively avoided. We recommend using the stacked-filter to enrich eDNA from water samples.